2022
DOI: 10.1093/jcbiol/ruac022
|View full text |Cite
|
Sign up to set email alerts
|

Formal re-establishment of Macrocheiridae Dana, 1851 (Decapoda: Brachyura: Majoidea) for the giant spider crabMacrocheira kaempferi(Temminck, 1836) based on a reappraisal of morphological and genetic characters

Abstract: The Japanese spider crab, Macrocheira kaempferi (Temminck, 1836), the largest living arthropod in the world, was originally placed in the family Majidae Samouelle, 1819 as a monotypic subfamily, Macrocheirinae Dana, 1851. While various authors have treated the taxon as belonging to its own superfamily, family, subfamily, or even tribe, the consensus of modern taxonomic system has for the most part considered it to be simply a genus within Inachidae MacLeay, 1838 (superfamily Majoidea Samouelle, 1819). Strangel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Based on the brachyuran fossil material studied at hand, the current view is that the earliest Eubrachyura (heterotremes) did not appear until the Early Cretaceous, but there are arguments for dating the first 'true crabs' to the Jurassic. This is what is suggested in our recent article (Guinot 2019), admittedly provocative and containing assumptions that will certainly prove false, but hopefully not in vain. For example, for the Late Jurassic Lecythocaridae Schweitzer & Feldmann, 2009, which do not appear to be podotreme crabs as currently believed, there is conclusive evidence to advocate for their eubrachyuran, probably majoid, affiliation, implying that the evolutionary history of Brachyura started much earlier than assumed (Guinot et al 2019: fig.…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…Based on the brachyuran fossil material studied at hand, the current view is that the earliest Eubrachyura (heterotremes) did not appear until the Early Cretaceous, but there are arguments for dating the first 'true crabs' to the Jurassic. This is what is suggested in our recent article (Guinot 2019), admittedly provocative and containing assumptions that will certainly prove false, but hopefully not in vain. For example, for the Late Jurassic Lecythocaridae Schweitzer & Feldmann, 2009, which do not appear to be podotreme crabs as currently believed, there is conclusive evidence to advocate for their eubrachyuran, probably majoid, affiliation, implying that the evolutionary history of Brachyura started much earlier than assumed (Guinot et al 2019: fig.…”
Section: Introductionmentioning
confidence: 54%
“…The evolutionary history of the Dorippoidea has been documented by fossils since the Early Cretaceous, and this early occurrence had confirmed that they were, with the Ma- Guinot D. joidea, the earliest splitting brachyuran branches (Luque 2015; Guinot et al 2013Guinot et al , 2019Charbonnier et al 2017;Guinot 2019;Vega et al 2019;Van Bakel et al 2020). Our view that Hymenosomatoidea is even more basal in Eubrachyura, with its relationship to Dorippoidea (Guinot 2011) apparently supported by consistent data sets, will be discussed in light of the recent discovery of even older hymenosomatoid fossil representatives, namely in the Barremian (Mendes et al 2022).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations